Analisis Strategi Humas Polrestabes Surabaya Dalam Mempertahankan Citra Kepolisian - Bari sarifudin; Rudi Febrianto; Deni Firmansyah; Dyva Claretta (CV. ITTC INDONESIA, 2022)
The image built by an institution needs to be maintained and developed, because the image certainly has an impact on public trust. The research entitled